Verb Root Identification in Nepali: An Alternative Perspective - Regmi, Bhim Narayan (Nepalese Linguistics, 2025)
Infinitive suffix -nu removal technique from the citation form for basic and those with the high vowels in the root among the intransitive-transitive pairs with CʌC CaC and CuC CoC structures for derived verb root identification among the contextual variants is practiced in Nepali. The other variants are related to the basic by vowel deletion and vowel lowering processes for basic and the derived roots respectively. This study presents an alternative perspective, i.e., the suffix -jo removal process to identify basic root and and taking transitive root with low vowel as basic among the intransitive-transitive pair. The other variants are related to the basic variant by vowel insertion and vowel heightening processes for basic and derived intransitive root respectively. This study is based on the secondary data. Principle of majority and principle of precedence support this perspective, and the vowel insertion and vowel heightening processes are found more plausible.